Understanding service failure and complaint management in marketing oriented organisations: a review - Mupemhi, Shepherd; Mupemhi, Ronicah; Feremba, Judity T. (Midlands State University, 2015)
Although marketing-oriented organizations have customer satisfaction as a major goal, it is difficult (if not impossible) to provide 'zero defects' services. Service failures can and do occur. This is largely due to the nature of services, especially in high contact service encounters. If service failures cannot be avoided then organizations must have clear service recovery strategies to prevent customer defections. Organisations must be able to solicit customer complaints and properly handle these complaints to keep the customer satisfied. This paper reviews existing literature on service failure and complaint management in marketing-oriented organizations and identifies the strategies that organisations can use to keep the customers satisfied after experiencing a service failure